Teachers’ experiences and challenges in implementing the Arabic language and Islamic values education program - Khalid B. Mustapha; Maria Ana T. Quimbo (Indonesian Journal of Social Sciences, 2026)
The Department of Education is implementing the Arabic language and Islamic values education (ALIVE) program to teach Muslim children about their religion, especially Islamic values, and the Arabic language. This is aligned with the Philippine government’s mandate to provide every Filipino the right to basic education regardless of religion, race, or political affiliation. Competent madrasah teachers or Asatidz are the main implementers of the ALIVE program. This study examined how Asatidz in the Division of Santa Rosa implements the program in terms of learning objectives, instruction, curriculum content, assessment, classroom management, and school leadership. This research used a descriptive-qualitative design to conduct in-depth interviews with five ALIVE teachers in Santa Rosa City, Laguna, Philippines. The findings show limitations in teacher training, accessibility of resources, and professional development, particularly in Arabic language and Islamic jurisprudence. The study provides value by emphasizing major problems in localized implementation and providing solutions to improve teacher training, resource allocation, and policy support. Finally, guaranteeing ALIVE's long-term viability necessitates a greater emphasis on teacher capacity building and system-level support to improve Muslim children's academic results.